UJI LISIS TELUR Ascaris lumbricoides SETELAH PEMBERIAN EKSTRAK ETANOL 70% JAHE MERAH (Zingiber officinale var rubrum) - Sri Kartini; Uswatun Hasanah (LPPM Universitas Abdurrab, 2022)
Worm infection is an environmental-based disease, can be transmitted through the soil or known as soil-transmitted helminth (STH). Infections caused by this parasite can be eradicated by administering synthetic drugs and herbal medicines. One of the plants that can be used as herbal medicine is red ginger (Zingiber officinale var rubrum). Red ginger (Zingiber officinale var rubrum) has one of the benefits, namely to treat intestinal worms. This study aimed to determine the lysis of Ascaris lumbricoides eggs after administration of 70% Ethanol Extract of Red Ginger (Zingiber officinale var rubrum). The method used in this research is a laboratory experiment. The results showed that at a concentration of 5% within 45 minutes there was no color change and there was no damage to the eggs of Ascarias lumbricoides, while at concentrations of 10% and 15% within 45 minutes it could cause changes in the color of the eggs and could lyse the eggs of Ascarias lumbricoides. Red ginger contains tannins, flavonoids, saponins and triterpenoids that are able to lyse eggs of Ascaris lumbricoides.